Currency risk management : a handbook for financial managers, brokers, and their consultants - Shoup, Gary. (Chicago : Glenlake Pub. Co. ; London : Fitzroy Dearborn, 1998)
This work shows how to capture the business of mid-sized companies - from the basic concepts of foreign exchange to prospecting the corporate client. The author shows the finer points of foreign exchange regimes recognized by the IMF and that exchange rates are a matter of government restrictions.
Includes index.
Includes bibliographical references (p. 231-233).
rua 07/06/17
Loan
Keywords: Foreign Exchange Futures; Risk Management